2012
DOI: 10.1108/17542411211214158
|View full text |Cite
|
Sign up to set email alerts
|

Career advancement and gender equity in healthcare management

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…One participant even indicated that he was demoted after declaration of disability while one argued that it took her longer to be promoted because the environment was not conducive for declaration. Several authors also found that promotion is one of the most evident advancement challenges faced by individuals living with a disability (Hussein, Manthorpe & Ismail, 2014;LaPierre & Zimmerman, 2012;Vickers, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…One participant even indicated that he was demoted after declaration of disability while one argued that it took her longer to be promoted because the environment was not conducive for declaration. Several authors also found that promotion is one of the most evident advancement challenges faced by individuals living with a disability (Hussein, Manthorpe & Ismail, 2014;LaPierre & Zimmerman, 2012;Vickers, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Given the developmental nature of the mentor/protégé relationship, mentoring affords the protégé certain outcomes. Protégés often benefit from tangible and objective outcomes of mentoring such as higher rates of promotion (Allen, Eby, Poteet, Lentz, & Lima, 2004;Eshner et al, 2001;LaPierre & Zimmerman, 2012) and higher salaries and bonuses (Allen et al, 2004;Burke & McKeen, 1996;Ramaswami, Dreher, Bretz, & Wiethoff, 2010). Promotions and higher salaries are often measures of career success (Allen et al, 2004), but perhaps a less tangible and more subjective outcome often attributed to career success is career satisfaction.…”
Section: Mentoring Outcomes For Protégésmentioning
confidence: 99%
“…Lapeirre found that nurses should have motive, adequate opportunity and time to participate in the programs resulting in career advancement. [30] Limitations Like other qualitative studies, the findings of the current study are probably situation-specific and hence of limited transferability.…”
Section: Discussionmentioning
confidence: 82%